2019
DOI: 10.1123/ijspp.2018-0336
|View full text |Cite
|
Sign up to set email alerts
|

Soccer Footedness and Between-Limbs Muscle Strength: Systematic Review and Meta-Analysis

Abstract: Purpose: Limb dominance and consequent between-limbs muscle strength in soccer players should be explored to determine a standard musculoskeletal profile to maintain and establish during screening protocols and postinjury rehabilitation. The primary aim of this review was to identify dominant- vs non-dominant-lower-extremity muscle-strength characteristics of healthy soccer players, with secondary aims to consider available between-limbs outcome measures and directions for future research. Methods: Preferred R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…However, it is assumed that they were symmetrical (>90% LSI) for the quadriceps strength. 65 Although musculoskeletal modelling allows for the prediction of in vivo muscle forces without invasive methods, it is not without limitations. Since measuring muscle forces in vivo during jumping is not feasible, we do not have a direct test for the accuracy of the computed muscle forces.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…However, it is assumed that they were symmetrical (>90% LSI) for the quadriceps strength. 65 Although musculoskeletal modelling allows for the prediction of in vivo muscle forces without invasive methods, it is not without limitations. Since measuring muscle forces in vivo during jumping is not feasible, we do not have a direct test for the accuracy of the computed muscle forces.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Each method provides different parameters of strength and has specific inherent weaknesses [ 5 ], such that strength assessments may not be equivalent between methods [ 4 ]. Although isokinetic strength measures have limited translation to sport-specific tasks, since these are rarely completed at an isokinetic pace [ 6 ], isokinetic assessments have several important advantages. These conducting assessments against a maximal resistance throughout the complete range of motion of a joint at different movement velocities [ 7 ], and the possibility of measuring torque [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the dominant limb is susceptible to injury not only due its higher kicking velocities and greater kicking frequency, but also for what the limb lacks relative to the non-dominant limb. Although isokinetic strength characteristics [ 11 ], lower extremity muscle crosssectional area [ 102 ], and power outputs [ 103 ] between limbs in previous studies have been reported to be relatively symmetrical, evidence of between-limb neuromuscular differences may be more telling. Coordinated neuromuscular tasks requiring multi-joint and multiplanar actions may help to elucidate between-limb differences.…”
Section: Discussionmentioning
confidence: 99%
“…footedness in soccer players) is an intrinsic trait that plays a significant role in soccer competition. It is often defined as the preferred kicking limb [ 11 ], and strongly influences soccer activity representing 82–84% of touches on average in the world’s most elite international competition, the World Cup [ 12 ]. Hägglund et al [ 7 ] observed increased rate of muscle strain injuries in the kicking leg, while Serner et al [ 13 ] reported greater incidence of dominant limb adductor injuries and kicking as a frequent mechanism of those injuries.…”
Section: Introductionmentioning
confidence: 99%